The Patient-Specific Implant Created with 3D Printing Technology in Treatment of the Irreparable Radial Head in Chronic Persistent Elbow Instability. (23rd October 2018) - Luenam, Suriya; Kosiyatrakul, Arkaphat; Hansudewechakul, Chanon; Phakdeewisetkul, Kantapat; Lohwongwatana, Boonrat; Puncreobutr, Chedtha
Abstract : Successful treatment of the chronic persistent elbow instability is a challenge for orthopedic surgeons. In this form, it is important to recognize and restore the osseous stabilizer in order to obtain the concentric reduction. In the present report, we describe a case of such injury with irreparable radial head treated with patient-specific radial head prosthesis which was created with 3D printing technology. To our knowledge, this is the first report in clinical use of this kind of prosthesis for the radial head fracture. At a 24-month follow-up visit, the patient was satisfied with the functional outcomes. The Mayo Elbow Performance Index (MEPI) increased from 20 points at the preoperative day to 85 points, and the patient-based Disabilities of the Arm, Shoulder, and Hand (DASH) was reduced from 88.33 points to 28.33 points. Due to the favorable result, replacement of the radial head with the patient-specific implant could be a useful treatment for the irreparable radial head in chronic persistent elbow instability.